Current orthopaedic practice a concise guide for postgraduate exams - Agarwal, Sanjeev (Tfm Pub., 2012)
Intended as an overview of orthopaedic practice, this title is of interest to orthopaedic surgeons in practice and to orthopaedic trainees - both specialist and basic surgical, in particular, orthopaedic specialist registrars in the UK preparing for the exam, or trainees in other countries at an equivalent stage of orthopaedic training.